Stroškovna učinkovitost zdravil za zdravljenje astme in alergij - Locatelli, Igor (Farmacevtski vestnik, 2013)
Guidelines for asthma treatment and prophylaxis recommend a stepwise management. Inhaled corticosteroids are the first choice treatment. When comparing inhaled corticosteroids there is no difference in terms of effectiveness. In such cases, a costminimisation approach can be used for comparing the costs of the evaluated health technologies. For patients, whom inhaled corticosteroid is considered appropriate, the least costly product is suitable. Regarding additional therapy with inhaled long-acting beta2-agonists, there was no significant difference in effectiveness when these were administered in a combination device as opposed to separate devices.
Keywords: asthma; astma; kortikosteroidi; therapy; zdravljenje